The effects of sleep deprivation and quality of sleep on cognitive performance and mental wellbeing - María Ósk Stefánsdóttir 1991- (2015)
Studies in the field of sleep have shown that sleep deprivation can affect mental wellbeing and furthermore that sleep is necessary for cognitive abilities. Few studies have examined the effect from both sleep duration and quality of sleep so the purpose of this study was to analyze the impact from both sleep duration and quality of sleep on mental health and cognitive performance. The present study used data from an ongoing research, monitoring cognitive workload using speech analysis. A total of 69 students in Reykjavík University were initially sampled. The sample contained 22 male (32%) and 47 female (68%). The participants age was from 20 years and older, 85% of the group where 20-30 years old. Two tasks were used to measure cognitive performance, Stroop test and the Ospan test. Questionnaires were used to measure psychological factors such as depression and anxiety and sleep behavior. Results from mixed ANOVA showed significant interaction between sleep duration and Stroop. Fixed factor ANOVA showed a significant interaction between quality of sleep and depression. No significant main effect or interactions were found between quality of sleep and sleep duration on anxiety and Ospan working memory. This results means that the worse quality of sleep participants got, the lower score on a Stroop attention test. Worse quality of sleep increases depression symptoms. Rannsóknir á sviði svefns hafa sýnt að svefnleysi geti dregið úr andlegri heilsu og ennfremur að svefn sé nauðsynlegur fyrir hugræna getu. Fáar rannsóknir hafa þó skoðað bæði lengd og gæði svefns í þessu samhengi. Tilgangur rannsóknarinnar var því að skoða áhrif gæði og lengd svefns á andlega heilsu og hugræna getu. Þessi rannsókn notast við gögn úr rannsókninni monitoring cognitive workload using speech analysis. Samtals 69 nemendur úr Háskólanum í Reykjavík tóku þátt í rannsókninni, 22 karla og 47 konur. Þátttakendur voru 20 ára og eldri en flestir voru á aldrinum 20-30 ára. Tvö próf voru notuð til að mæla hugræna getu, annars vegar Stroop ...